The Conceptualist Ends of Writing and the End of Conceptualism. - Armand, Louis (CounterText, 2020)
This essay examines the convergence of conceptualist poetics with evolutionary code as a form of 'becoming alien'. The focus is Christian Bök's The Xenotext project: an attempt at translating a 'short verse about language and genetics', using a chemical alphabet, into a DNA sequence implanted into the genome of a polyextremophile bacterium capable of enduring conditions in outerspace. Bök describes the project as, 'in effect, engineering a life-form so that it becomes not only a durable archive for storing a poem, but also as an operant machine for writing a poem – one that can persist on the planet until the sun itself explodes ...'. The concrete, constraint-based character of Bök's project evokes a mode of writing between posthumanist aesthetics and a positivist grammatology by turns deconstructive and itself requiring of deconstruction.